STUDI EVALUASI PELAKSANAAN ASSESMEN BERBASIS KELAS DI SEKOLAH MENENGAH PERTAMA - Eufrasia Jeramat; Fransiskus Nendi; Silfanus Jelatu; Alberta Parinters Makur; Yohanes Kumiawan (Universitas Negeri Malang, 2019)
Abstract: This study aims to determine the effectiveness of the implementation of class-based assessments in Langke Rembong Secondary School viewed from the context, input, process, and product (CIPP) variables. This research includes quantitative evaluative analysis. The sample in this study was the principal: Deputy headmaster, teachers of Mathematics, and Natural Sciences courses. Data was collected using interviews, observation, and documentation. Data analyzed by descriptive analysis. Determine the effects of implementing a class-based assessment, the raw score is transformed into a T-score then verified into the Glickman prototype. Results of the reviews that the performed of class-based assessments in SMP Negeri II Langke are relatively active seen from the variables of context, input, process, and input with the results in quadrant III (+ - + +). There is because the CIPP evaluation used refers to the assessment standard. The researcher suggested that in the future, the teacher of Langke Rembong Junior High School II should always improve their competencies and resources through training activities. Keywords: Class-Based Evaluation; Implementation; Assessment Study Abstract: Penelitian ini bertujuan untuk mengetahui efektivitas pelaksanaan penilaian berbasis kelas di Sekolah Menengah Langke Rembong dilihat dari variabel konteks, input, proses, dan produk (CIPP). Penelitian ini termasuk analisis evaluatif kuantitatif. Sampel dalam penelitian ini adalah kepala sekolah: Wakil kepala sekolah, guru Matematika, dan kursus Ilmu Pengetahuan Alam. Data dikumpulkan menggunakan wawancara, observasi, dan dokumentasi. Data dianalisis dengan analisis deskriptif. Menentukan efek dari penerapan penilaian berbasis kelas, skor mentah diubah menjadi skor-T kemudian diverifikasi ke dalam prototipe Glickman. Hasil review yang dilakukan penilaian berbasis kelas di SMP Negeri II Langke relatif aktif dilihat dari variabel konteks, input, proses, dan input dengan hasil di kuadran III (+ - + +). Ada karena evaluasi CIPP yang digunakan mengacu pada standar penilaian. Peneliti menyarankan bahwa di masa depan, guru SMP II Langke Rembong harus selalu meningkatkan kompetensi dan sumber daya mereka melalui kegiatan pelatihan.